2023
DOI: 10.1590/1518-8345.6746.3960
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress in nursing students: relationship with screen time, diet and physical activity

Abstract: Objective: to determine the prevalence of anxiety and depression symptoms, as well as their association with screen time, diet and physical activity, in a cohort comprised by nursing students. Method: a descriptive and cross-sectional study conducted with a sample of 648 Nursing students. The instruments used were the Hospital Anxiety and Depression Scale, the short version of the International Physical Activity Questionnaire and the Spanish Healthy Eating Index (Índice de Alimentación Saludable Español, IASE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…The study showed that dietary nutrition played an independent mediating role between physical activity and anxiety, accounting for 24.9% of the total effect value. Previous studies have found that physical activity and dietary behaviors have potentially positive effects on psychological distress (Glozah et al, 2018;Ramón-Arbués et al, 2023). It has always been known that physical activity has a reasonable effect on anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…The study showed that dietary nutrition played an independent mediating role between physical activity and anxiety, accounting for 24.9% of the total effect value. Previous studies have found that physical activity and dietary behaviors have potentially positive effects on psychological distress (Glozah et al, 2018;Ramón-Arbués et al, 2023). It has always been known that physical activity has a reasonable effect on anxiety.…”
Section: Discussionmentioning
confidence: 99%